How Barney Glaser and Classic Grounded Theory Have changed and Impacted my Life - Barry Chametzky (Grounded Theory Review: An International Journal)
I could never have imagined, how, in 2011 or so, my life would have been positively affected by one person and a research design in my dissertation. At that time, I was starting to write my dissertation and was planning on using an ethno-phenomeno-case study-ology as my research design. Clearly, I was confused and naive. But I connected with an online cohort where I learned about classic grounded theory. I’d like to share some instances of how Barney Glaser and classic grounded theory as a research design have changed and impacted my life.